Impacts of Indoor Air Quality on Working‐Age Populations' Subjective Well‐Being: Evidence From China Labor Dynamics Survey. - Zhou, Zhengqing; Ai, Hongshan; Zhang, Xi (Kyklos, 2025)
Outdoor air pollution can affect physical labor productivity and mental health, but it remains to be studied how indoor air quality (IAQ) exposure affects working‐age populations' subjective well‐being and physical health. Here, the first evidence of a link between IAQ and the subjective well‐being of working‐age populations has been provided using the dataset from a longitudinal survey in China. Using household ventilation as an instrument variable (IV) of IAQ revealed that IAQ improvements increased working‐age populations' subjective well‐being and life satisfaction by significantly affecting their physical health. Our analysis shows that an increase in IAQ by one standard deviation improves working‐age populations' subjective well‐being by 0.041 standard deviations. The marginal willingness to pay for IAQ is approximately 98.09 CNY. Compared with outdoor air quality, the impact of IAQ on well‐being and life satisfaction is more conspicuous. The results are robust to a variety of alternative specifications. For developing countries, improving IAQ is a new channel toward enhancing life quality, with lower economic and social costs.